Stopping 'Pass the Parcel' with practice-based student learning : Establishing education governance frameworks between academia and industry to facilitate collaborative design of practice-based experiences and constructive alignment with discipline standards and targeted learning outcomes : final report. - Henderson, Amanda (Australia. Dept of Education, Skills and Employment, 2020)
Graduate capability and employability are regarded as critical success factors for degree programs by universities, industry and the students. A common response by the higher education sector to the demands for employability has been developing and furthering work-based experiences for academic credit within degree programs. The interest of the university in optimising work-based learning is imperative given the recognised benefits to professionalism and student employment. Defining Work Integrated Learning (WIL): WIL is most frequently used when referring to the broad range and diverse experiences that students engage in these work placements (Ferns, Campbell and Zegwaard 2014). Patrick et al. (2008) recognise WIL as ‘an umbrella term for a range of approaches and strategies that integrate theory with the practice of work within a purposefully designed curriculum’, and a WIL placement as ‘a type of work integrated learning that requires the student to be situated in the workplace’ (p. iv). [From Henderson and Trede 2017]. The breadth of experiences and opportunities that are associated with WIL are extensive and, as such, the issues that accompany WIL are diverse. Therefore, a decision was made to focus the Fellowship specifically on work-based learning and accompanying assessment (the key to governance) so that discussions were targeted and clear. This ensured that Fellowship outcomes were both useful and practical. Focus of this Fellowship: Work-based learning that supports student learning through learning and teaching strategies that occur in real world contexts under organised supervision and counts towards academic credit as part of a compulsory component of a degree course. [Publisher summary, ed]